SISTEM MONITORING KUALITAS UDARA BERBASIS NODEMCU ESP8266 DENGAN METODE FUZZY LOGIC (SOFTWARE) - Diemas Ibnus Pasedja; Mohammad Yanuar Hariyawan (ABEC Indonesia, 2021)
Riau Province is an area that has the largest peatland area on the island of Sumatra, namely ± 4.04 million hectares or 56.1% of the total area of ​​peatland in Sumatra (Wahyunto et.al., 2003). Illegal forest burning which often occurs in the province of Riau has resulted in worsening air quality and a haze that hits Riau Province almost every year. The creation of an air quality monitoring system specifically placed in the Caltex Riau Polytechnic environment can assist in making smoke emergency decisions. This system is designed using the NodeMCU ESP8266 as the Master Control Unit (MCU) and uses several sensors, including the GP2Y1010AU0F as a detector for airborne PM10 levels, the DHT11 sensor as a temperature and humidity detector, the MQ-7 sensor as a detector for carbon monoxide levels in the air. Sensor data is sent to the database and displayed on a local website page (localhost) in realtime. PM10 sensor testing has an average error rate with a comparison tool of 9.56%, a temperature sensor of 8.42% and a humidity sensor of 2.89%. With this system, the entire campus academic community will be able to find out information on air quality in real time and help the campus in making smoke haze emergency decisions in the Riau Caltex Polytechnic environment. Keywords: NodeMCU ESP8266, realtime, website, haze, localhost